Improved total organic fluorine methods for more comprehensive measurement of PFAS in industrial wastewater, river water, and air. (15th May 2023) - Forster, Alexandria L.B.; Zhang, Ying; Westerman, Danielle C.; Richardson, Susan D.
Highlights: New AOF and EOF methods quantify TOF in industrial wastewater, river water, and air. TOF method captures up to 99% more organic fluorine than target LC-MS/MS. Higher recoveries for a larger mix of 39 PFAS compounds. EOF method utilizes a new type of SPE cartridge, combining WAX phase with graphitized carbon black. EOF gave slightly higher recovery for 39 PFAS standards and lower LODs and LOQs. Abstract: Per- and polyfluoroalkyl substances (PFAS) are high-profile environmental contaminants, many having long persistence in the environment and widespread presence in humans and wildlife. Following phase-out of perfluorooctane sulfonate (PFOS) and perfluorooctanoic acid (PFOA) in North America and restrictions in Europe, PFAS replacements are now widely found in the environment. While liquid chromatography (LC)-mass spectrometry (MS) is typically used for measurement, much of the PFAS is missed. To more comprehensively capture organic fluorine, we developed sensitive and robust methods using activated carbon adsorption, solid phase extraction, and combustion ion chromatography (CIC) to measure total organic fluorine (TOF) in industrial wastewaters, river water, and air. Two extraction techniques, adsorbable organic fluorine (AOF) and extractable organic fluorine (EOF), were optimized and compared using 39 different PFAS, including replacements, such as GenX and perfluorobutanesulfonate. Our AOF method achieves 46–112% and 87% recovery for individual PFAS and PFAS mixtures, respectively, with 0.5 µg/L limit of detection (LOD) for a 50 mL sample volume and a 0.3 μg/L LOD for a 500 mL sample volume . Our EOF method achieves 72–99% and 91% recovery for individual PFAS and PFAS mixtures, respectively, with 0.2 µg/L LOD for a 500 mL sample volume and 0.1 μg/L LOD for 1200 mL. In addition to 39 anionic PFAS, two zwitterionic PFAS and two neutral PFAS were evaluated using the optimized TOF methods. Substantially higher TOF values were measured in industrial wastewater, river water, and air samples compared to LC-MS/MS, demonstrating how TOF methods provided a more comprehensive measurement of the total PFAS present, capturing known and unknown organic fluorine. Graphical abstract: Image, graphical abstract